2003
DOI: 10.1021/nl034795u
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Independent Electrical Switching in Pt/Organic Monolayer/Ti Devices

Abstract: Electronic devices comprising a Langmuir−Blodgett molecular monolayer sandwiched between planar platinum and titanium metal electrodes functioned as switches and tunable resistors over a 102−105 Ω range under current or voltage control. Reversible hysteretic switching and resistance tuning was qualitatively similar for three very different molecular species, indicating a generic switching mechanism dominated by electrode properties or electrode/molecule interfaces, rather than molecule-specific behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
280
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(284 citation statements)
references
References 18 publications
3
280
0
1
Order By: Relevance
“…All PCM measurements are performed at room temperature. As reported previously [7,8,16], when the devices are in a high conductance state (R<~100kΩ), we observed individual nanoscale conductance peaks, or "switching centers", in response to mechanical pressure applied by an AFM tip (Fig. 1b, upper insets); when the same devices are switched "off", these peaks disappear (Fig.…”
supporting
confidence: 84%
“…All PCM measurements are performed at room temperature. As reported previously [7,8,16], when the devices are in a high conductance state (R<~100kΩ), we observed individual nanoscale conductance peaks, or "switching centers", in response to mechanical pressure applied by an AFM tip (Fig. 1b, upper insets); when the same devices are switched "off", these peaks disappear (Fig.…”
supporting
confidence: 84%
“…It was demonstrated that the electromechanical switching occurs within a variety of physical environments. [3][4][5][6]26 However, it was also observed that an intrinsically molecular switching cannot be observed in solid-state experiments based on purely metallic electrodes, 8,9 which signifies that the molecule-electrode barriers are required in the tunnel junction experiments. One possible reason is the formation of metallic filaments that would mask any molecular signature when the molecules are directly contacted to the electrodes.…”
Section: ͑1͒mentioning
confidence: 99%
“…While the voltage-gated conformational change of the molecules between the off-state GSCC and the on-state MSCC was proposed as the switching mechanism, 3-6 the molecular origin of the switching was questioned 7 as seemingly contradictory experiments appeared. [8][9][10] Indeed, differentiating a molecularly inherent switching from a stochastic one is a difficult task, 11 because the charge transport in molecular scale junctions is strongly influenced by the moleculeelectrode contacts and conformational fluctuations of molecules. [12][13][14][15] In a recent work, 16 employing realistic catenane monolayer models sandwiched between Au͑111͒ electrodes , we explicitly showed that the electrical switching ͑between on and off͒ can originate from the energetic movement of frontier orbitals that accompanies the structural switching of the molecule ͑between GSCC and MSCC, respectively͒.…”
mentioning
confidence: 99%
“…Recent experiments indicate that the electrical resistance switching in metal/molecule/metal junctions may not depend on the particular molecular specie but on the state of the interface and its modification with an applied electric field. [6] In our previous work we have predicted the existence of a giant electroresistance (GER) effect in ferroelectric tunnel junctions. [4] Using a simple model we investigate how the change in potential profile caused by modification of the electric dipole of the molecule and the charge state of the interface produces a very large change in resistance.…”
Section: Theorymentioning
confidence: 99%